IMPROVING MOTHERS’ KNOWLEDGE AND AWARENESS OF HELMINTH INFECTION PREVENTION THROUGH BOOKLET-BASED HEALTH EDUCATION AT A COMMUNITY HEALTH CENTRE - Dela Riadi; Siti Nuriyatus Zahrah; Isniani Ramadhani (LPPM Universitas Flores, 2026)
Helminth infections remain a significant public health problem in Indonesia, particularly among young children. The high prevalence of helminth infection increases the risk of stunting, anaemia, and malnutrition. Prevention efforts are often hindered by limited public awareness and the misconception that helminth infection is not a serious health issue. This community service program aimed to improve mothers’ knowledge and awareness of helminth infection prevention through booklet-based health education at a community health centre. The participants comprised 12 mothers of young children who visited Community Health Centre X in Depok. The activity was conducted on April 24, 2026, using health counselling, group discussion, and question-and-answer sessions supported by educational booklets. Qualitative evaluation results indicated an improvement in mothers’ understanding of risk factors, transmission, and preventive measures related to helminth infections. In addition, community health volunteers demonstrated increased confidence and readiness to deliver health education to the wider community. In conclusion, booklet-based health education was effective in enhancing mothers’ knowledge and awareness, and community-based educational strategies can support the prevention of helminth infections among young children.